Becoming a ‘Fortress of Love’ for the Motherland: The Role of Local Sufi Order in Indonesia - Tasmuji, Tasmuji; Al Amin, Ainur Rofiq; Zahro, Ahmad; Muhibbin, Muhibbin (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
This article discusses the views of the Indonesian Ṣiddīqīyah Sufi order on Indonesian independence and national identity. This tarekat has offered a new perspective to the study of Sufism and its relationship with national politics in Indonesia. This article discusses how members of the Ṣiddīqīyah tarekat view Indonesian independence, the role of its founding fathers, and love for the motherland. This qualitative research uses a phenomenological approach focusing on Mircea Eliade’s sacred and profane theory, utilizing literature sources and interviews with several figures in the tarekat to collect the relevant data. The data analysis found that the Ṣiddīqīyah views national independence as related to the dimension of barakah and achieved through the efforts of the Walisongo. The tarekat is also aware of the importance of loving the motherland, which is one of its core teachings, as reflected in the phrase “Love for the motherland is part of the faith” decorating their communal buildings.